Probiotic Characterization of Honey Bee-Associated Lactic Acid Bacteria and Their Impact on Colony Growth - Subramanian Pradeep; Y. S. Johnson Thangaraj Edward; Vangili Ramasamy Saminathan; Angappan Suganthi; Murugaiyan Senthilkumar; Narayanan Manikanda Boopathi; Venkatachalam Karthik; Bimal Kumar Sahoo; Mohammad Ikram (Probiotics and Antimicrobial Proteins, 2026)

A Review on Potato Dormancy Prediction and Sprouting Detection Methods: Advancements in Analytical Technologies for Postharvest Physiology - T. Senthilkumar; S. Ramalingam; R. K. Goraya; U. C. Lohani; C. B. Singh (Potato Research, 2026)

Energy-Efficient Wireless Monitoring and Automated Aeration System for Sustainable Sugar Beet Pile Conditioning - M. Singla; Sunday J. Olakanmi; T. Senthilkumar; S. S. Panigrahi; C. B. Singh (Sugar Tech, 2026)

Surface treatment and service temperature effects on the performance of hybrid polymer composites reinforced with aluminized glass, bamboo fiber, and bagasse carbon quantum dots - S. Ramu; N. Senthilkumar; B. Deepanraj (Journal of the Indian Academy of Wood Science, 2026)

Isolation and complete genome analysis of Porcine Parvovirus 1 from swine with reproductive failure in southern India - P. Mohanapriya; S. Parthiban; K. Reshma; M. Parthiban; M. Murugan; A. Ramesh; K. Senthilkumar; P. Raja; P. Jalantha; Jagadish Hiremath; S. S. Patil; M. Kalyana Chakravarthi; et al. (Archives of Microbiology, 2026)

Impact of lifestyle on salivary microbiota composition and antibiotic resistance in adult periodontitis patients - Saranya S; Saveetha Priya V; Roja B; Shreejaa C; SenthilKumar N; Chellapandi P (Antonie van Leeuwenhoek, 2026)

A Walking Type Self-Propelled Single-Row Carrot Harvester-Cum-Detopper for Hilly Region - T. Senthilkumar; S. Syed Imran; G. Manikandan; R. Sanjay Krishnan (Agricultural Research, 2026)

Exploring the Neuroprotective Role of the Sulfonamide Derivative KM11 in Ethidium Bromide-induced Demyelination in Zebrafish Model Through Modulation of Antioxidant and Inflammatory Cytokine Pathways - Karthikeyan Ramamurthy; Magesh Santhanakrishnan; S. Madesh; Prasannakumar Raja; Senthilkumar Palaniappan; Bader O. Almutairi; Mikhlid H. Almutairi; Muhammad Obaid M. Alotaibi; Yahya Madkhali; Manikandan Palanisamy; Kathiravan Muthu Kumaradoss; Jesu Arockiaraj (Molecular Neurobiology, 2026)

A comprehensive review of biomass utilization for sustainable biofuel and biocomponent development - Jih-Hsing Chang; S. Selvaraj; S. Manikandan; S. Nagarani; Arunkumar Senthilkumar; Melvin S. Samuel; Ethiraj Selvarajan; Ashwini J. John; Mohanraj Kumar (Biomass and Bioenergy, 2025)

Dual scheme biocatalytic pre-treatment and AHL mediated quorum sensing activation to accelerate biofilm formation: A multi-perspective technology for the sustainable biodegradation of marine microplastics - Naveen Nair; Shivangi Dutta; S. Tarun; Muneeswari Rajasekaran; Subhan Kumar Pal; Ravikrishnan Vinu; Senthilkumar Balakrishnan; Ramani Kandasamy (Chemical Engineering Journal, 2025)

Unraveling the genetic potential of wild rice (Oryza rufipogon) for sustainable food security - Himaswetha Rajan; K. N. Ganesan; S. Manonmani; C. Gopalakrishnan; G. Senthilkumar; R. Suresh (Genetic Resources and Crop Evolution, 2025)

The Impact Assessment of Mechanized Transplanting of Sugarcane Settlings Using Economic Surplus Approach - K. P. Saha; Dushyant Singh; T. Senthilkumar; S. P. Singh; Rajni Jain; Manoj Kumar; V. Bhushanababu (Sugar Tech, 2025)

Lactic Acid Bacteria: A Probiotic to Mitigate Pesticide Stress in Honey Bee - Subramanian Pradeep; Johnson Thangaraj Edward Y. S.; Suganthi Angappan; Senthilkumar Murugaiyan; Saminathan Vangili Ramasamy; Narayanan Manikanda Boopathi (Probiotics and Antimicrobial Proteins, 2025)

Efficacy of 6-nitrobenzo[d]thiazol-2 Amine Derivative (N3) in Mitigating PTZ-Induced Epileptic Conditions Via Modulation of Inflammatory and Neuroprotective Pathways in-vivo Zebrafish - Karthikeyan Ramamurthy; S. P. Ramya Ranjan Nayak; S. Madesh; Siva Prasad Panda; K. Manikandan; Rajakrishnan Rajagopal; Ahmed Alfarhan; Senthilkumar Palaniappan; Ajay Guru; M. K. Kathiravan; Jesu Arockiaraj (Journal of Neuroimmune Pharmacology, 2025)

Genotype × Environment Interaction Analysis and Simultaneous Selection Using AMMI, BLUP, GGE Biplot and MTSI Under Drought Condition in Sweet Potato - K. H. Gowda; V. B. S. Chauhan; M. Nedunchezhiyan; C. Pradeepika; K. M. Senthilkumar; V. Chandra; G. Byju; M. R. Sahoo; K. Pati; R. Arutselvan (Journal of Soil Science and Plant Nutrition, 2025)

Anticancer potential of Calligonum comosum L.’Her. and Calligonum crinitum Boiss plants from United Arab Emirates - Wesam Khader; Mohamed K. Kayali; Tawfik M. Taj Eddin; Abdul Hadi S. S. S. Alameri; Mughair Abdul Aziz; Jaleel Kizhakkayil; Annadurai Senthilkumar; Ayesha S. Al Dhaheri; Abdul Jaleel (Advances in Traditional Medicine, 2025)

Unveiling the diversity of gut microbes in green lacewings (Chrysopidae: Neuroptera) and their role as protagonist in nutrition - N. Karkuzhali; Y. S. Johnson Thangaraj Edward; N. Chitra; M. Senthilkumar; J. Ramalingam (Archives of Microbiology, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Mitigation of gentamycin induced acute kidney injury due to benzothiazole derivatives N1 and N5: Antioxidant and renoprotective mechanisms in-vivo zebrafish - S. Madesh; Senthilkumar Palaniappan; Anand Aravind; Avra Sau; Mikhlid H. Almutairi; Bader O. Almutairi; Ilavenil Soundharrajan; S. Karthick Raja Namasivayam; Kathiravan Muthu Kumaradoss; Jesu Arockiaraj (Toxicology Letters, 2025)

Assessing potential of teosinte in diversification of maize germplasm for kernel protein - S. Varalakshmi; Narendra Kumar Singh; Navneet Pareek; V. Senthilkumar (Genetic Resources and Crop Evolution, 2025)

Assessing the influence of hydrogeochemical characteristics and microbial communities on monsoon dynamics in groundwater quality in north Chennai city, India - S. Syed Ahamudul Rafeek; N. Mohamed Basith; M. Mohamed Hanipha; Meera Moydeen Abdul Hameed; S. Senthilkumar (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Recent advancements in nanotechnological approaches for pollution monitoring and environmental sustainability - J. Manjunathan; M. Revathi; H. Sowmya; S. S. Meenambiga; R. Sudha; B. Prakash; Senthilkumar Nangan; Lalitha Gnanasekaran; N. Thirumalaivasan (Clean Technologies and Environmental Policy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Recent advancements in carbon/metal-based nano-catalysts for the reduction of CO2 to value-added products - Arun Kumar Senthilkumar; Mohanraj Kumar; Melvin S. Samuel; Selvarajan Ethiraj; Mohd Shkir; Jih-Hsing Chang (Chemosphere, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Tackling toxicity and stability using eco-friendly metal-halide ion substituted perovskite nanocrystals for advanced display color conversion - Maithili K. Rao; M. Selvakumar; M.G. Mahesha; Selvaraj Paramasivam; M.S. Santosh; S. Senthilkumar; Shiva Kant; Sami Rtimi (Chemical Engineering Journal, 2024)

Interactive behavior of cadmium ions onto polyethylene microplastics in aquatic system - D. M. Reddy Prasad; B. S. Naveen Prasad; R. Senthilkumar; K. Saravana Kumar; S. Manickkam (International Journal of Environmental Science and Technology, 2024)

Mapping of groundwater availability in dry areas of rural and urban regions in India using IOT assisted deep learning classification model - Senthilkumar S; A. Basi Reddy; Anna Alphy; Jayaraj Velusamy; Indra J; Manikandan Rajagopal (Groundwater for Sustainable Development, 2024)

Polyethylene terephthalate waste derived nanomaterials (WDNMs) and its utilization in electrochemical devices - J. Manjunathan; K. Pavithra; Senthilkumar Nangan; S. Prakash; Kuldeep K. Saxena; Kuldeep Sharma; Khursheed Muzammil; Deepak Verma; Jenita Rani Gnanapragasam; R. Ramasubburayan; M. Revathi (Chemosphere, 2024)

Shrimp classification for white spot syndrome detection through enhanced gated recurrent unit-based wild geese migration optimization algorithm - L. Ramachandran; S. P. Mangaiyarkarasi; A. Subramanian; S. Senthilkumar (Virus Genes, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

Waste plastics derived nickel-palladium alloy filled carbon nanotubes for hydrogen evolution reaction - Senthilkumar Nangan; Thirumalaivasan Natesan; Wiwittawin Sukmas; Manunya Okhawilai; Kaliyamoorthy Justice Babu; Prutthipong Tsuppayakorn-aek; Thiti Bovornratanaraks; Tawan Wongsalam; Vrince Vimal; Hiroshi Uyama; Abdullah M. Al-Enizi; Lavish Kansal; et al. (Chemosphere, 2023)

Ziziphus mauritiana-derived nitrogen-doped biogenic carbon dots: Eco-friendly catalysts for dye degradation and antibacterial applications - Subramani Rajapandi; Senthilkumar Nangan; Thirumalaivasan Natesan; Anuj Kumar; Govindaraj Dharman; M. Pandeeswaran; Deepak Verma; Mohd Ubaidullah; Bidhan Pandit; Navdeep Dhaliwal; Satbir S. Sehgal; Rajavel Rangappan; et al. (Chemosphere, 2023)

Genetic diversity analysis of Indian Cassava (Manihot esculenta Crantz) accessions using morphological and molecular markers - Swathy Sivan; Arya K; Sheela M N; Revathi B S; Prakash Krishnan B S; Senthilkumar K Muthusamy (South African Journal of Botany, 2023)

Halotolerant Nodule Rhizobial and Passenger Endophytes Alleviates Salinity Stress in Groundnut (Arachis hypogaea L.) - G. Oviya; Anandham Rangasamy; Manikandan Ariyan; R. Krishnamoorthy; M. Senthilkumar; N. O. Gopal; S. Thiyageshwari; S. Meena; S. Vincent (Journal of Plant Growth Regulation, 2023)

Azadirachta indica leaf extract mediated silver nanoparticles impregnated nano composite film (AgNP/MCC/starch/whey protein) for food packaging applications - Harish Pandian; Senthilkumar; Venkata Ratnam M; Naveenkumar M; Samraj S (Environmental Research, 2023)

Implementation of Micro-Nanobubbles Technology for the Treatment of Domestic Wastewater: Experimental Study - G. Senthilkumar; S. Lakshmi Sankar (Water, Air, & Soil Pollution, 2023)

Isolation and genetic analysis of Porcine circovirus 2 in southern India evidences high circulation of Porcine circovirus 2d genotype - S. Parthiban; A. Ramesh; Anbu Kumar Karuppannan; G. Dhinakar Raj; S. Hemalatha; M. Parthiban; K. Senthilkumar; D. Balasubramaniyam; R. Sumanth Kumar; S. Ranganatha; Chintu Ravishankar (Molecular Biology Reports, 2022)

Effective batch and column remediation of zinc(II) from synthetic and electroplating effluents using biochar from brown alga - R. Senthilkumar; Krishnan Saravanakumar; D. M. Reddy Prasad; B. S. Naveen Prasad; Feroz Shaik (International Journal of Environmental Science and Technology, 2022)

Molecular evidence of porcine circovirus 3 infection in swine: first report in southern India - S. Parthiban; A. Ramesh; G. Dhinakar Raj; Anbu Kumar Karuppannan; S. Hemalatha; M. Parthiban; Chintu Ravishankar; K. Senthilkumar; D. Balasubramaniyam (VirusDisease, 2022)

Reuse of Uncontrolled Burnt Bagasse Ash from Sugar Industries with Waste Rubber Powder in Construction: A Waste to Wealth Approach for Sugar Mills - K. S. Teja; R. Senthilkumar; G. Athira; A. Bahurudeen (Sugar Tech, 2022)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Biostimulant activity of sulfated polysaccharide extract from red seaweed Halymenia dilatata on yield of Mung bean in greenhouse conditions - S. Vinoth; P. Gurusaravanan; M. Arun; M. Saradhadevi; N. Senthilkumar; P. Gowtham; S. R. Sivakumar (Journal of Applied Phycology, 2021)

Ramping up of SARS CoV-2 testing for the diagnosis of COVID-19 to better manage the next phase of pandemic and reduce the mortality in India - Senthilkumar Natesan; Ragini Bhatia; Aarthi Sundararajan; Kuldeep Dhama; Yashpal S. Malik; Kranti Vora (VirusDisease, 2020)

Comparative bioefficacy of Bacillus and Pseudomonas chitinase against Helopeltis theivora in tea (Camellia sinensis (L.) O.Kuntze - M. Suganthi; S. Arvinth; P. Senthilkumar (Physiology and Molecular Biology of Plants, 2020)

Impact of landuse on the groundwater quality along coastal aquifer of Thiruvallur district, South India - S. Senthilkumar; B. Gowtham; M. Sundararajan; S. Chidambaram; J. Francis Lawrence; M. V. Prasanna (Sustainable Water Resources Management, 2018)

Effects of geological structures on groundwater flow and quality in hardrock regions of northern Tirunelveli district, southern India - M Senthilkumar; R Arumugam; D Gnanasundar; D S C Thambi; E Sampath Kumar (Journal of Earth System Science, 2015)

Preliminary Analysis of Polycyclic Aromatic Hydrocarbons in Air Particles (PM10) in Amritsar, India: Sources, Apportionment, and Possible Risk Implications to Humans - Simerpreet Kaur; Kurunthachalam Senthilkumar; V. K. Verma; Bhupander Kumar; Sanjay Kumar; Jatinder Kaur Katnoria; C. S. Sharma (Archives of Environmental Contamination and Toxicology, 2013)

Perfluoroalkyl Substances in the Blood of Wild Rats and Mice from 47 Prefectures in Japan: Use of Samples from Nationwide Specimen Bank - Sachi Taniyasu; Kurunthachalam Senthilkumar; Eriko Yamazaki; Leo W. Y. Yeung; Keerthi S. Guruge; Kurunthachalam Kannan; Nobuyoshi Yamashita (Archives of Environmental Contamination and Toxicology, 2013)

Methylobacillus rhizosphaerae sp. nov., a novel plant-associated methylotrophic bacterium isolated from rhizosphere of red pepper - M. Madhaiyan; S. Poonguzhali; M. Senthilkumar; D. Pragatheswari; K.-C. Lee; J.-S. Lee (Antonie van Leeuwenhoek, 2013)

Viral and bacterial aetiologies of epithelial ovarian cancer - S. Shanmughapriya; G. SenthilKumar; K. Vinodhini; B. C. Das; N. Vasanthi; K. Natarajaseenivasan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

In vitro cytotoxicity and induction of apoptosis by ruthenium(II) complexes in HL-60 and K-562 - S. Bhattacharya; Subhas S. Karki; R. Suresh; L. Manikandan; G. P. Senthilkumar; M. Gupta; Upal K. Mazumder; R. Balaji; K. Murali (Medicinal Chemistry Research, 2012)

Influence of hydraulic retention time in a two-phase upflow anaerobic sludge blanket reactor treating textile dyeing effluent using sago effluent as the co-substrate - M. SenthilKumar; G. Gnanapragasam; V. Arutchelvan; S. Nagarajan (Environmental Science and Pollution Research, 2011)

Recycle in upflow anaerobic sludge blanket reactor on treatment of real textile dye effluent - G. Gnanapragasam; M. Senthilkumar; V. Arutchelvan; P. Sivarajan; S. Nagarajan (World Journal of Microbiology and Biotechnology, 2010)

Stability Assessment of Injectable Castor Oil-Based Nano-sized Emulsion Containing Cationic Droplets Stabilized by Poloxamer–Chitosan Emulsifier Films - S. Tamilvanan; B. Ajith Kumar; S. R. Senthilkumar; Raj Baskar; T. Raja Sekharan (AAPS PharmSciTech, 2010)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Characterization of multiple promoters and transcript stability in the sacB–sacC gene cluster in Zymomonas mobilis - V. Senthilkumar; J. Rajendhran; S. J. W. Busby; P. Gunasekaran (Archives of Microbiology, 2009)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Induction of endophytic colonization in rice (Oryza sativa L.) tissue culture plants by Azorhizobium caulinodans - M. Senthilkumar; M. Madhaiyan; S. P. Sundaram; H. Sangeetha; S. Kannaiyan (Biotechnology Letters, 2008)

Effects of Copper Sulfate and Copper Nitrate in Aquatic Medium on the Restoration Potential and Accumulation of Copper in Stem Cuttings of the Terrestrial Medicinal Plant, Portulaca Oleracea Linn - S. Mohanapriya; P. Senthilkumar; S. Sivakumar; M. Dineshkumar; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Plant Growth–Promoting Methylobacterium Induces Defense Responses in Groundnut (Arachis hypogaea L.) Compared with Rot Pathogens - M. Madhaiyan; B. V. Suresh Reddy; R. Anandham; M. Senthilkumar; S. Poonguzhali; S. P. Sundaram; Tongmin Sa (Current Microbiology, 2006)

Copper Availability and Accumulation by Portulaca Oleracea Linn. Stem Cutting - R. Deepa; P. Senthilkumar; S. Sivakumar; P. Duraisamy; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Polychlorinated Dibenzo- p -Dioxins, Dibenzofurans, and Dioxin-Like Polychlorinated Biphenyls in Livers of Birds from Japan - K. Senthilkumar, N. Iseki, S. Hayama, (Archives of Environmental Contamination and Toxicology, 2002)

Isolation, PCR based identification, and sensitivity pattern of environmental mycobacteria from leprosy and tuberculosis patients - D. Saravanakumar; N. Elangeswaran; S. Senthilkumar; G. Vanaja; S. Kamakshiammal; C. Chandrasekar; C. N. Deivanayagam; Manjula Sritharan; V. Sritharan (Indian Journal of Clinical Biochemistry, 2000)

Accumulation Features of Polychlorinated Biphenyls and Organochlorine Pesticides in Resident and Migratory Birds from South India - S. Tanabe; K. Senthilkumar; K. Kannan; A. N. Subramanian (Archives of Environmental Contamination and Toxicology, 1998)